Community-based product standardization education to strengthen human resource capacity of The Peduli Pesisir forest farmer group in Beras Basah Village, Langkat District, North Sumatra - Bejo Slamet (Journal of Saintech Transfer, 2025)
Forest Farmers Group (KTH) Peduli Pesisir has played an active role in coastal conservation through mangrove forest rehabilitation and the utilization of fishery products. Although it is well known locally and has many customers, the lack of proper standardization is a major obstacle to improving the competitiveness and economic value of its products.  This community service activity was carried out using an educational approach and discussions. Participants in the activity were members of the KTH Peduli Pesisir directly involved in food production processes. The methods used included education on hygiene, sanitation, and good manufacturing practices (GMP) in food production in the micro, small, and medium enterprises (MSMEs) and the importance of product standardization. The questionnaire results show that participants’ perceptions consistently improved after participating in the program, particularly regarding the importance of product standardization, quality assurance, and consumer trust. Participants also felt that implementing standardization not only facilitates market access but also increases product value and helps meet distribution and certification requirements. Enhancing KTH Peduli Pesisir's capacity in product standardization is a crucial foundation for sustainable business development. The implementation of good quality standards not only improves product safety but also opens access to larger markets and enhances consumer trust. The combination of education and active discussion plays a significant role in promoting economic independence among coastal communities, alongside efforts to preserve the environment.